Validity of Rapid Diagnostic Test Kit Keeping Light Microscopy in Diagnosing Malaria in Febrile patients - Hafiz Muhhammad Matloob, Zobia Rehman, Wasia Salam, Amna Shaquat, Sidra Sonia, Aiza Asghar, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Malaria is the common health problematic disease and it causes major number of mortality and morbidity. It must be diagnosed accurately and rapidly. A rapid and correct diagnosis can reduce the sufferings. So it’s essential to establish an appropriate and reliable laboratory procedure for malaria diagnosis. Microscopic examination of blood film is taken as the gold standard method. Aim: To assess the reliability and validity of rapid diagnostic test kit, so that the rapid and a cost effective diagnostic method may be adopted for the timely diagnosis, and treatment may be offered to patients Methodology: 350 patients having history of fever were taken for this Cross sectional validation study. Tested by ICT rapid diagnostic kit for detection of malarial antigen and results were then compared with gold standard microscopic results Results: for the 350 suspected patients the rate of positivity and negativity were 60% and 40% respectively by microscopic examination and for ICT for detection of malarial antigen were 58% and 42% respectively. Specificity and sensitivity for antigen detection by ICT when it was compared with microscopy of blood smear was 95% and 93.33% respectively. Its overall diagnostic accuracy was good and it was 94% Conclusions: ICT for antigen can diagnose malaria reliably. It is rapid; simple has good sensitivity and specificity. It can detect very low level of parasitic infection and can be performed at point of care and for screening at mass level. No special equipment or high level of setup and skills needed for it.